Dye Sensitized Solar Cells with X% Cu-TiO2 Photoelectrode Sensitized from Syzygium malaccense - Fajriah, Nurul; Yuniarti, Elvan; Saptari, Sitti Ahmiatri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
Abstract: Dye Sensitized Solar Cell preparation with x% Cu-TiO2 photoelectrode sensitized from Jamaica guava leaf dye (Syzygium malaccense) has been successfully made. This DSSC composed of x% Cu- TiO2 Photoelectrode synthesized by the doctor blading method with variation concentration Cu dopant at 0%, 1%, and 5%. Sensitizer (dye) made with technique maceration; electrolyte solution used an iodine solution, counter electrode with a carbon layer made from a candle flame; all the components are then arranged like a sandwich. The layers were characterized by X-ray diffraction to determine the phase, structure, and crystal size. X-ray diffraction characterization was carried out on all x% Cu-TiO2 layers. X-ray diffraction results show that has identified TiO2 anatase phase compound with a tetragonal crystal structure and has an average crystal size obtained from calculations using the Williamson Hall method for 0%, 1%, and 5% Cu doping fractions respectively are 60.28 nm, 43.32 nm, and 53.32 nm. UV-Vis's spectrophotometric characterization was carried out to determine the optical properties of the dye, and the results showed that Jamaica guava leaf dye has light absorption at a wavelength between 400-700 nm with a band gap energy of 1.728 eV. Furthermore, the current-voltage (IV) characterization was carried out to determine the efficiency of the solar cell. Based on the research results, the addition of Cu dopants as Photoelectrode can increase the efficiency of DSSC at a certain concentration. The highest efficiency achieved is 0.0036 % at 1% Cu doping concentration.